The Impact of X (Formerly Twitter) on the Social Well-Being of University Students - Hannah Blessed Padde (Uganda Christian University, 2024)
This research study explores the relationship between the use of X (formerly Twitter) and the social well-being of university students. This study made use of a qualitative research study and in-depth open-ended interviews with six university students who frequently use X and revealed that students used X to seek and consume information, social interaction and self-expression. The data collected was analyzed using a thematic analysis to identify patterns in how students use X, reasons they use X and the positive and negative impacts X has had on their social well-being. This study’s findings are relevant in understanding the crucial dynamics for developing the necessary strategies to overcome the negative impact of social media platforms and make the best use of them by maximizing the benefits.